Changes in the Masticatory Apparatus and Remodelling of Facial Bones - Kaszycka, Katarzyna (Anthropological Review, 1983)
Tensions related to the function of mastication are one of the important factors in formation of bones of the face. The present author has investigated influence of tooth loss (lack of molars) and changes in distribution of forces in bones of the face resulting there from on formation of selected cranioscopic features (fossa canina, sulcus praenasalis, zygomatic notch). A null hypothesis stating that there is no relation between changed distribution of forces due to tooth loss and form of certain cranioscopic features cannot be rejected on grounds of the results of the present work.